2015
DOI: 10.4103/2006-8808.185654
|View full text |Cite
|
Sign up to set email alerts
|

Elective bowel surgery with or without prophylactic nasogastric decompression: A prospective, randomized trial

Abstract: Introduction:Routinely postoperative nasogastric decompression was done until the nasogastric drainage is minimal, reoccurrence of bowel sounds and passing flatus. But prolonged nasogastric intubation is associated with complications like basal atelectasis due to poor cough reflux, loss of electrolytes and increased patient morbidity.Aims and Objectives:To study the need for routine use of nasogastric tube post operatively in bowel surgeries with reference to (1) Return of bowel movements (2) Compare the incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
2
8
0
1
Order By: Relevance
“…The time of removal of NG tube in control group ranged from 2 to 6 days., whereas, the first postoperative bowel sound was heard earlier (2.02 days) in study group as compare to the control group (2.96 days). 10 Similar results were noted with Cheadle et al 15 Which is again like what noted in our study. Bradshow BG 16 , showed one day early passage of flatus following removal of NG tube on operative day, study patients were also discharge one day before the control group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The time of removal of NG tube in control group ranged from 2 to 6 days., whereas, the first postoperative bowel sound was heard earlier (2.02 days) in study group as compare to the control group (2.96 days). 10 Similar results were noted with Cheadle et al 15 Which is again like what noted in our study. Bradshow BG 16 , showed one day early passage of flatus following removal of NG tube on operative day, study patients were also discharge one day before the control group.…”
Section: Discussionsupporting
confidence: 93%
“…Stimulation of the posterior pharynx often causes gagging and vomiting. 9 Many randomized control trial, like H. G. Vinay, (p<0.000) 10 , Ming-Hui Pang (p<0.05 for diet, p=0.02 for flatus) 11 , Nadia Shamil 12 , Nadim Khan (p>0.005) 13 , have revealed that nasogastric (NG) tube decompression can safely be omitted from routine postoperative care.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a later study showed no improvement in defaecation or oral tolerance within a goal‐directed fluid protocol. One RCT tested the effect of avoiding routine NGT intubation, which demonstrated improved gastrointestinal function (time to oral tolerance 3·1 versus 4·8 days) and reduced complications such as pneumonia. Other interventions have included stoma stimulation with thickened saline before reversal, abdominal massage and dextromethorphan (usually a cough suppressant).…”
Section: Resultsmentioning
confidence: 99%
“…Vinary 10 , for elective bowel surgery with or without prophylactic nasogastric decompression also had similar demographic groups. Nasogastric tube intolerance was common complaint noted by Michele Tanguy 8 which is also the chief complaint in control group in our study.…”
Section: Discussionmentioning
confidence: 86%